Quantitative Detection of Low-Copy-Number mRNAs Differing at Single Nucleotide Positions. (January 2003) - Stenman, J.; Lintula, S.; Rissanen, O.; Finne, P.; Hedström, J.; Palotie, A.; Orpana, A.
Accurate analysis of mRNA expression levels of SNPs, highly homologous genes, and splicing variants requires techniques capable of quantifying low-copy-number mRNAs differing at single nucleotide positions. We have used an RT-PCR-based technique based on co-amplification of closely related target mRNA transcripts and assessed the effect of the stochastic distribution of low-copy-number templates on sampling variation when quantifying rare mRNA transcripts. The technique was optimized for maximal sensitivity to enable the analysis of samples containing a subpopulation of target cells and small microdissected samples. We demonstrate that the input level of template molecules is a critical determinant of the achievable assay precision. A minimum of approximately 50 molecules of template is required to discriminate between 2-fold differences in the expression levels of two transcripts. At levels above 1000 molecules of input template, the stochastic effects on sampling variation become negligible.